Static and dynamic strategies to understand C programs by code annotation - Berón, Mario (2008)
In this paper we present strategies aimed at understanding program written in C language. These strategies use the code annotation technique to extract information from programs. With these strategies we can define the architecture of a comprehension system that allows us to integrate multiple views important to understand the application under analysis. These views are presented in diferent abstraction levels, and the user can navigate between them. Both features (views and navigation) are useful because they can be used to carry out various program understanding approaches, similar to our mental models. In order to implement these features we define: a scheme to recover static and dynamic information; and an way to manage this information. Furthermore, with the purpose to facilitate the program understanding process we describe a procedure aimed at relating the problem and program domains denominated BORS (Behavioral-Operational Relation Strategy).